QoE-aware video cooperative caching and transmission mechanism based on TWDM-PON and C-RAN - Dapeng WU; Xue LI; Hongxia LI (Tongxin xuebao)
The quality of user experience suffers from performance deterioration dramatically due to the explosively growing data traffic.To improve the poor performance of cell-edge users and heavy-load cell users,which caused by dense network and load imbalance respectively,an QoE-aware video cooperative caching and transmission mechanism in cloud radio access network was proposed.Cooperative gain-aware virtual passive optical network was established to provide cooperative caching and transmission for video streaming by adopting collaborative approach in optical domain and wireless domain.Furthermore,user experience for video streaming,bandwidth provisioning and caching strategy were jointly optimized to improve QoE,which utilized the methods of dynamic caching in optical domain and buffer level-aware bandwidth configuration in wireless domain.The results show that the proposed mechanism enhances the quality of user experience and effectively improves the cache hit rate.